KESENJANGAN UPAH ANTAR JENDER DI INDONESIA: GLASS CEILING ATAU STICKY FLOOR? (GENDER WAGE GAP IN INDONESIA: GLASS CEILING OR STICKY FLOOR?) - Hennigusnia Hennigusnia (Research Centre for Population, Indonesian Institute of Sciences, 2014)
This study looked the gender wage gap in Indonesia from 2008-2012. In addition to looking at the wage gap average level, the study also looked at the wagegap at different quantile of the wage distribution, so it can be known whether the wage gap widened at the top of the wage distribution (indicative of glass ceilings) or widened at the bottom of the wage distribution (sticky floors). This study used data Sakernas 2008-2012 to estimate the wage equation of men and women using OLS standard. Then, the Oaxaca-Blinder decomposition method (1973) is used to determine the magnitude of the gender wage gap based on gender that caused by the characteristics factors (explained effect) and the discrimination factor (unexplained effects). As for determining the gender wage gap in different quantile of the wagedistribution using quantile regression and applying decomposition Machado Mata (2005). This study found that the gender wage gap was still dominated by factors that can not be explained (Unexplained) and was indicated as discrimination, both at the average level and in each quantile of the wage distribution. This study also found evidence of sticky floor in Indonesia.